Evaluation of two protocols for chemical restraint in guinea pigs (Cavia porcellus). - Júnior, Gilberto Serighelli; Comassetto, Felipe; Stiehl, Maite Zanotto; Oleskovicz, Nilson (Archives of Veterinary Science, 2024)
Abstract: This study evaluated the cardiorespiratory parameters, analgesia, sedation depth and duration, and recovery quality in guinea pigs undergoing elective castration, using dexmedetomidine or xylazine combined with esketamine hydrochloride and morphine. In a crossover study, guinea pigs (Cavia porcellus) (n=8), 9 months and 650 g (p = 0,3831) received xylazine (1 mg/kg), esketamine (10 mg/kg), and morphine (0,5 mg/kg) (GXIL), or dexmedetomidine (5 mcg/kg), esketamine (10 mg/kg), and morphine (0,5 mg/kg) (GDEX) intramuscularly at a two-week interval. Cardiorespiratory parameters, including respiratory rate (RR), heart rate (HR), SpO2, and rectal temperature (RTºC), were recorded at baseline (M0) and every 5 minutes post-administration (M5 to M60). Sedation depth was assessed via ear/toe pinch response, jaw tone, righting reflex, posture, palpebral reflex and reaction to manipulation, based on the criteria established by D’OVÍDIO et al. (2017). Statistical analysis included the Shapiro-Wilk test, unpaired t-test, two-way repeated measures ANOVA, and non-parametric tests (Kruskal-Wallis, Wilcoxon, Mann-Whitney U). GXIL induced more profound sedation, with significant differences in ear/toe pinch response and jaw tone compared to GDEX. HR and RR significantly decreased in the GXIL group, with an average reduction of 13,6% in HR and 32,6% in RR. GDEX demonstrated less sedation depth and a milder decrease in RR. Both protocols were effective and safe for chemical restraint in guinea pigs, though GXIL provided deeper sedation and greater cardiorespiratory depression than GDEX. However, GDEX maintained a more stable cardiorespiratory profile, suggesting it. Nonetheless, both treatments provided minimal cardiorespiratory alterations, demonstrating their safety for use.